The first cave-dwelling species of Whiteheadiana Perrault, 1994 (Carabidae: Clivinini) from Brazil - Benjumea, Daniela Hoyos; Ferreira, Rodrigo Lopes; Vieira, Letícia (Zootaxa, 2023)
The new species Whiteheadiana thaisae sp. nov., is described and illustrated. This is the first species of the genus known for Toca do Gonçalo cave, located in Campo Formoso municipality, Bahia state, northeastern Brazil. The new species differs from the other species of the genus by presenting frontal lateral projections two times longer than eyes; frons with two parallel carinae deeply notched near the clypeus, shallow toward the gena, and it is a restricted eventual cave-restricted. Ecological notes about habitat and conservation issues are provided.